Implementation of Islamic Religious Education Values as an Effort to Enhance Social Awareness in Community Life - M Rajani; A. Hariri Aikon Noor; Umi Rauhun; Muhammad Wahyudi; Juwita Juwita; Mubarak Mubarak (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the implementation of Islamic Religious Education values in improving social awareness within the community. Social awareness is an important aspect of social life, especially in building harmonious relationships among individuals. However, the decline in social concern, mutual cooperation, and empathy in society has become a challenge in the modern era. Therefore, Islamic Religious Education values are expected to become a solution in shaping a caring and responsible society. This research used a qualitative descriptive approach with observation, interviews, and documentation as data collection techniques. The participants consisted of community leaders, religious leaders, and members of the community involved in religious and social activities. The study found that the implementation of Islamic Religious Education values through religious studies, social service activities, charity programs, and communal worship activities significantly contributed to increasing social awareness among community members. The results indicate that Islamic values such as mutual help, empathy, honesty, and responsibility are capable of fostering solidarity and strengthening social relationships in society. Thus, Islamic Religious Education plays an important role in shaping a socially responsible and morally aware community.